Penerapan Pembelajaran Berdiferensiasi dalam Mewujudkan Merdeka Belajar Pada Pembelajaran Sosiologi - Nurlizawati Nurlizawati; Dendy Marta Putra; Eka Asih Febriani; Ike Sylvia; Junaidi Junaidi (Universitas Sriwijaya, 2023)
The change of the 2013 curriculum into a “merdeka” curriculum is an unavoidable policy. In West Sumatra there are 36 schools that serve as “penggerak” schools. The “penggerak” schools are a pilot in implementing the curriculum merdeka. The merdeka curriculum emphasizes the thinking of KH Dewantara ing roso sung tulodo, which is a teaching and learning process that must facilitate students to grow according to their nature. In the Merdeka curriculum, this is known as differentiated learning. The implementation of differentiated learning encounters several obstacles, both from teachers as facilitators and students as subjects in education, therefore the authors are interested in researching the application of differentiated learning in realizing independent learning. The method used in this research is qualitative research with data collection techniques through interviews, observation and documentation. The data analysis technique used is the interactive analysis technique by Miles and Hubermans. The results of this study indicate that differentiated learning can be done using varied learning models, varied learning media and assessment techniques based on students' learning styles.